Endogenous Adenosine Modulation of 22Na Uptake by Rat Brain Synaptosomes - Ribeiro, Joaquim Alexandre (2003)
To evaluate if endogenous extracellular adenosine influences sodium channel activity in nerve terminals, we investigated how manipulations of extracellular adenosine levels influence 22Na uptake by rat brain synaptosomes stimulated with veratridine (VT). To decrease extracellular adenosine levels, adenosine deaminase (ADA) that converts adenosine into an inactive metabolite was used. To increase extracellular adenosine levels, we used the adenosine deaminase inhibitor erythro-9(2-hydroxy-3-nonyl) adenine (EHNA), as well as the inhibitor of adenosine transport, nitrobenzylthioinosine (NBTI). ADA (0.1–5?U/ml) caused an excitatory effect on 22Na uptake stimulated by veratridine, which was abolished in the presence of the adenosine deaminase inhibitor erythro-9(2-hydroxy-3-nonyl) adenine (EHNA, 25?µM). Both the adenosine uptake inhibitor nitrobenzylthioinosine (NBTI, 1–10?µM) and the adenosine deaminase inhibitor EHNA (10–25?µM) inhibited 22Na uptake by rat brain synaptosomes. It is suggested that adenosine is tonically inhibiting sodium uptake by rat brain synaptosomes.